Analytical Study of Selected Urdu Books Written on Christianity - Muhammad Ikramullah; Muhammad Junaid (Journal of Islamic and Religious Studies, 2016)
Christianity is the religion from the Hazrat Essa (A.S) the Holy Prophet of Allah. Christians believe that Christianity is a perfect religion and this religion save them from hell, and this religion is revealed from Allah. Christian knows that their ideology based upon Hazrat Essa (A.S) and they relate themselves towards Hazrat Essa (A.S). Different books in different languages have written on the Christianity like English, Arabic, Persian and other languages there are many books written on Christianity in Pakistani national language Urdu and the books written in many languages have translated in Urdu. The analysis put forward on Christianity in Urdu written books, one thing is clear that which author writes a good, topic on Christianity and on the other hand by studying Christianity students and readers feel easy and will understand about these books easily and search the relevant material easily. This article shows the analytical study of books written on Christianity in Urdu and translation from other languages nominated Urdu books.